2009
DOI: 10.1007/s10592-009-0031-x
|View full text |Cite
|
Sign up to set email alerts
|

Historical and recent genetic bottlenecks in European grayling, Thymallus thymallus

Abstract: Sharp declines in population size, known as genetic bottlenecks, increase the level of inbreeding and reduce genetic diversity threatening population sustainability in both short-and long-term. We evaluated the presence, severity and approximate time of bottlenecks in 34 European grayling (Thymallus thymallus) populations covering the majority of the species distribution using microsatellite markers. We identified footprints of population decline in all grayling populations using the M ratio test. In contrast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 98 publications
(134 reference statements)
4
40
0
Order By: Relevance
“…These results are similar to those found by Swatdipong et al (2010) who also found most of the populations they investigated to have effective population sizes less than 50. These small sizes have important conservation implications as populations with an Ne of less than 50 are widely considered to be at risk of inbreeding depression (Franklin 1980;Rieman and Allendorf 2001).…”
Section: Population Bottlenecks and Effective Population Sizesupporting
confidence: 90%
See 2 more Smart Citations
“…These results are similar to those found by Swatdipong et al (2010) who also found most of the populations they investigated to have effective population sizes less than 50. These small sizes have important conservation implications as populations with an Ne of less than 50 are widely considered to be at risk of inbreeding depression (Franklin 1980;Rieman and Allendorf 2001).…”
Section: Population Bottlenecks and Effective Population Sizesupporting
confidence: 90%
“…These small sizes have important conservation implications as populations with an Ne of less than 50 are widely considered to be at risk of inbreeding depression (Franklin 1980;Rieman and Allendorf 2001). Due to the high site fidelity found among grayling, however, low Ne estimates may reflect the Ne of a subset of the population rather than that of the population as a whole (Swatdipong et al 2010). To investigate this possibility in our UK data set, we combined the two population samples from the Wylye and estimated Ne using ONeSamp.…”
Section: Population Bottlenecks and Effective Population Sizementioning
confidence: 99%
See 1 more Smart Citation
“…Our MSVAR analysis suggested that the contemporary common carp population size is roughly 3% of its historical size and that the population decline started 17000-49000 years ago, based on linear and/or exponential model. Similar values of strong ancient population decline were also reported for the African buffalo, 8% (Heller et al 2008) or the golden eagle, 3% (Bourke et al 2010) and even stronger for European grayling, 0.03-1.2% (Swatdipong et al 2010). Thus, an ancient genetic bottleneck that occurred thousands of years ago, could be the result of postglacial colonization of Europe from the Caspian basin refugia (Kohlmann et al 2003) or some ecological or climatic changes.…”
Section: Discussionsupporting
confidence: 72%
“…The possibility of an increased probability of extinction because of decreased genetic variance is a significant concern of conservation biology as evidenced by the number of papers focused on this phenomenon in journals such as Conservation Genetics, Conservation Biology and Animal Conservation: a search using the term ''bottleneck*'' under the division of Biodiversity Conservation in web of science produced 402 papers, 342 of which were published in the last 10 years. Analysis of genetic variation using molecular markers in populations passing through such population bottlenecks has shown significant loss of genetic variation: examples include eutherian mammals (Bonnell and Selander 1974;Neumann et al 2004;Culver et al 2008;Durrant et al 2009;Haanes et al 2010;Corti et al 2011;Fenderson et al 2011;Ricanova et al 2011;Sastre et al 2011), marsupials (Sinclair et al 2002;Cardoso et al 2009), birds (Bellinger et al 2003;Munoz-Fuentes et al 2005;Funk et al 2010;Kuro-o et al 2010), amphibians (Schoville et al 2011), fish (Consuegra et al 2005;Earl et al 2010;Swatdipong et al 2010) and plants (Jacquemyn et al 2010). Despite the loss of molecular variation after passing through a bottleneck numerous species (but not all-see, for example, Heber and Briskie 2010) have shown few ill effects and their populations have expanded and persisted: for example, the Northern elephant seal (Hoelzel 1999;Weber et al 2000;Hoelzel et al 2002), the kakerori, an endemic bird of the Cook Islands (Chan et al 2011), the Seychelles kestrel (Groombridge et al 2009), the skink, Oligosoma suteri (Miller et al 2011), the butterfly, Parnassius apollo (Habel et al 2009) and the stingless bee Melipona scutellus (Alves et al 2011).…”
Section: Introductionmentioning
confidence: 99%